Coronavirus disease 2019 crisis and intentional injuries: now is not the time to erode alcohol control policies - Lange, Shannon; Probst, Charlotte; Rehm, Jürgen (Canadian journal of public health, 2020)
In Canada, and elsewhere, the coronavirus disease 2019 (COVID-19) crisis has resulted in a social, economic, and alcohol policy environment that is likely to contribute to a rise in intentional injuries, whether interpersonal or self-directed violence. Heavy drinking has been identified as an important risk factor for intentional injuries, and with the erosion of alcohol control policies on alcohol availability, heavy drinking is likely to increase. During a time of social isolation, economic loss, psychological distress, and reduced access to health services and support networks, all of which are catalytic factors for both intentional injuries and heavy alcohol use, what is needed is individualized and population-based preventive interventions aimed at reducing alcohol consumption, rather than decisions to increase certain forms of alcohol availability.